A Study on the Cultural Popularization and Dissemination Effects of Mobile Games Themed on the Culture of Guishan Han Tomb in Xuzhou - Wei, Zhang; Chaetnalao, Atithep (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This study investigates the intergenerational inheritance gap of the cultural heritage of the Han Tomb in Guishan, Xuzhou, paying special attention to the differences between young individuals (14 to 35 years old) and middle-aged and elderly people in cultural awareness, media preference and value recognition. The purpose of the study is threefold: 1) to understand the cognitive characteristics and media usage habits of young people on Han tomb culture; 2) Compare the communication preferences of different age groups; 3) Explore the potential of mobile game design in communication and intergenerational cultural transmission. In this study, the young population and the middle-aged and elderly population were compared and analyzed by quantitative research. Data were collected by questionnaire and analyzed by SPSS. The findings are as follows: 1) Young people prefer communication modes that emphasize entertainment and social interaction, while middle-aged and elderly people prefer authoritative interpretation and static display-this difference fails to meet the interaction expectations of young people; 2) Digital technologies, such as interactive experience and virtual display, have significantly increased the participation of young people in the culture of Han tombs; 3) By using digital tools, integrating subculture elements and promoting intergenerational dialogue, the cultural narrative of Han tomb heritage can evolve from being dominated by middle-aged and elderly people to being jointly created and shared by generations. The conclusion of this study is that innovative communication channels through digital technology can effectively bridge the generation gap in the inheritance of cultural heritage and provide a practical way to promote intergenerational cultural integration.